2021
DOI: 10.3390/life11080787
|View full text |Cite
|
Sign up to set email alerts
|

Photorhabdus sp. ETL Antimicrobial Properties and Characterization of Its Secondary Metabolites by Gas Chromatography–Mass Spectrometry

Abstract: Entomopathogenic nematodes (EPNs) are known to be highly pathogenic to insect pests, due to their associated symbiotic bacteria, which produce virulence factors, exo-enzymes and other harmful secondary metabolites to conquer, kill, and degrade their insect hosts. However, these properties are not fully characterized. This study reports on the antimicrobial activities of Photorhabdus sp. strain ETL, symbiotically associated to an insect pathogenic nematode, Heterorhabditis zealandica, against human pathogenic b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 76 publications
1
11
0
Order By: Relevance
“…Furthermore, GC coupled to high-resolution time-of-flight mass spectrometry (HRTOF-MS) is one of the recent innovations and robust metabolomic technologies, with improved mass resolutions and data collection rates [ 24 , 25 ]. As shown in previous studies, GC-HRTOF-MS is a potent analytical technique that can effectively screen various metabolites in microorganisms with high sensitivity and excellent results [ 26 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, GC coupled to high-resolution time-of-flight mass spectrometry (HRTOF-MS) is one of the recent innovations and robust metabolomic technologies, with improved mass resolutions and data collection rates [ 24 , 25 ]. As shown in previous studies, GC-HRTOF-MS is a potent analytical technique that can effectively screen various metabolites in microorganisms with high sensitivity and excellent results [ 26 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…coli O157 (ATCC93111) as model strains of gram-positive and gram-negative species. Lulamba et al (2021) mentioned that he extracted this compound, and he also indicated that this compound is pathogenic to a wide range of insects.…”
Section: Discussionmentioning
confidence: 99%
“…In EPNs infected insects, these endosymbionts defend the host cadaver from the invading microbiome by the secretion of a variety of compounds possessing antibiotic activities. These metabolites are also used as biocontrol negotiators for the management of viruses, fungi, nematodes, and insects (Lulamba et al 2021). The bioactive components produced by Xenorhabdus and Photorhabdus play an essential role in the biological transformation of host insects.…”
Section: Role Of Endosymbionts As Biocontrol Agentsmentioning
confidence: 99%